Dynamics of network formation in aqueous suspension RAFT styrene/divinylbenzene copolymerization - Miguel A. D. Gonçalves (2013)
Experimental studies concerning the RAFT copolymerization of styrene and commercial divinylbenzene were performed in order to assess the use of controlled radical polymerization for the production of non-conventional polymer networks. Aqueous suspension polymerizations were carried out in stirred batch reactor and changes of a few operation parameters were tried in order to assess their effect on key product properties: reaction temperature, initial ratio monomer/RAFT agent, monomer dilution in the organic phase and crosslinker content in the monomer mixture were changed along the experimental program. Polymerizations were extended beyond the gel point in order to synthesize gel beads. The effect of different commercially available RAFT agents (e.g. S-thiobenzoyl thioglycolic acid and two trithiocarbonates) on network process formation was also studied. Dynamics of gel formation was measured using size exclusion chromatography with refractive index and light scattering detection. Iodine chloride titration yielded pendant double bonds concentration. In-line and off-line FTIR-ATR measurements were also performed in order to obtain information concerning the kinetics of formation and final structure of the gels.